ANALITYCAL HIERARCHY PROCESS (AHP) METHOD IN SUPPORTING THE DECISION SYSTEM OF DETERMINING THE ACCEPTANCE OF INSTANT DIRECT AID COMMUNITY - Wonsang Ryu (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
So far, the determination of recipients of direct public assistance funds (BLSM) is still not accurate. Therefore we need a decision support system application program that can assist in making a decision accurately and quickly to get accurate selection results. The method used in this application is the Analytical Hierarchy Process (AHP) where the classification process is carried out in a hierarchical manner, providing a comparison value for each criterion to determine the criteria value. This research resulted in an application of a decision support system for determining the receipt of direct assistance funds while the community used the Analytical Hierarchy Process (AHP) method. In this application the criteria and sub-criteria can be determined according to the indicators that exist in each region and can be grouped based on the selection period. The results of testing this application show a fairly accurate percentage and can be used to determine BLSM recipients.